Structure-based virtual screening methods for the identification of novel phytochemical inhibitors targeting furin protease for the management of COVID-19 - Kumar Tiwari, Prashant; Chouhan, Mandeep; Mishra, Richa; Gupta, Saurabh; Chaudhary, Anis Ahmad; Al-Zharani, Mohammed; Ahmed Qurtam, Ashraf; Nasr, Fahd A.; Jha, Niraj Kumar; Pant, Kumud; Kumar, Mukesh; Kumar, Sanjay (Frontiers in Cellular and Infection Microbiology, 2024)
COVID-19, caused by SARS-CoV-2 virus, is a highly contagious respiratory disease with widespread societal impact. The symptoms range from cough, fever and pneumonia to complications affecting various organs, including heart, kidneys and nervous system. Despite various on-going efforts, there is no effective drug, been developed to stop the spread of the virus. Although, various types of medications used in bacterial and viral diseases have previously been employed to treat COVID-19 patients, but their side effects have also been observed. The way SARS CoV-2 infects human body is very specific as its spike protein plays an important role. The S subunit of virus spike protein cleaved by human proteases, such as furin protein, is an initial and important step for its internalization into human host. Keeping this context, we attempted to inhibit the furin using phytochemicals, that could produce minimal side effects. For this, we screened 408 natural phytochemicals from various plants having anti-viral properties, against Furin protein, and molecular docking and dynamics simulations were performed. Based on binding score, top three compounds (Robustaflavone, Withanolide, and Amentoflavone) were selected for further validation. MM/GBSA energy calculations revealed that Withanolide has lowest binding energy of -57.2 kcal/mol followed by Robustaflavone, and Amentoflavone with binding energy -45.2, and -39.68 kcal/mol respectively. Additionally, ADME analysis showed drug-like properties for these three lead compounds. Hence, these natural compounds Robustaflavone, Withanolide, and Amentoflavone may have therapeutic potential for the management of SARS-CoV-2 by targeting furin.